2011
DOI: 10.1590/s1678-91992011000100012
|View full text |Cite
|
Sign up to set email alerts
|

Leptospiral antibodies in wild boars (Sus scrofa) bred in Brazil

Abstract: Abstract:In the recent years, the wild boar (Sus scrofa) trade has increased in Brazil. The present study aimed to detect Leptospira spp. infection in 308 blood samples from wild boars bred in São Paulo state, Brazil. The microscopic agglutination test (MAT) was performed using 29 serovars. Sixty three (63; 20.45%) animals tested positive against the serovars Hardjo (29/63; 46.0%), Copenhageni (11/63; 17.4%), Pomona (8/63; 12.7%), Pyrogenes (4/63; 6.3%), Wolfii (4/63; 6.3%), Autumnalis (3/63; 4.7%), Icterohaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In São Paulo state, Brazil, 63 out of 308 (20.54%) boars raised were reagent, which indicates that these captive animals can represent a source of infection to humans and other animals (20).…”
Section: Wild Animal Aspectmentioning
confidence: 99%
“…In São Paulo state, Brazil, 63 out of 308 (20.54%) boars raised were reagent, which indicates that these captive animals can represent a source of infection to humans and other animals (20).…”
Section: Wild Animal Aspectmentioning
confidence: 99%
“…foot-and-mouth disease), and so impact the country's agricultural economy. In this context, several studies have shown that the species is involved in enzootic cycles of zoonoses [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%